Digital Transformation in the Transportation and Logistics Industry - Kurniadi, Wahyu (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Digital transformation is reshaping the transportation and logistics industry by leveraging emerging technologies to improve operational efficiency, enhance customer experiences, and stay competitive in a globalized market. This article explores the impact of digital transformation on the transportation and logistics sector in Indonesia, focusing on key technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), blockchain, and cloud computing. The adoption of these technologies has led to real-time tracking, data-driven decision-making, and improved supply chain integration. However, challenges such as high initial investment, a lack of digital expertise, and cybersecurity concerns remain significant barriers to widespread adoption. Using a qualitative descriptive approach, this article examines various case studies and literature to highlight how Indonesian companies are implementing digital solutions and the resulting benefits and obstacles. The findings indicate that while digital transformation offers substantial advantages, its success relies on strategic planning, investment in workforce development, and strong industry partnerships.